Salmonella transport and persistence in soil and plant irrigated with artificially inoculated reclaimed water: climatic effects - Palacios M.P.; Lupiola P.; Fernandez-Vera F.; Mendoza V.; Tejedor M.T. (Water saving in Mediterranean agriculture and future research needs [Vol. 2], 2007)
Secondary effluent chlorination is extended but there are incidences in which Salmonella survive, contaminating reclaimed water ponds. Specific site conditions influence pathogens existence and persistence. The aim of the experiments was to increase the scientific information on the climatic and soil effects on pathogens transport and survive under agricultural conditions. Five pots were irrigated using a secondary effluent artificially inoculated with Salmonella. To study the effect of competence with soil bacteria, plates with sterilized soil were also tested. Radiation effect was also studied by blocking UV light. Stems and leaves, three different soil depths (surface, 0.15 and 0.45 m) and plates were sampled. As result of the radiation effect, less bacterial counts on plant were obtained during the day. But during the night, Salmonella was able to re-grow, depending on the nocturnal temperatures. After 3 weeks in the field, Salmonella was still detected in plant samples. The solar radiation caused Salmonella death in soil samples in spring while natural soil bacteria competence was the main factor affecting in autumn. Soil was able to filtrate Salmonella, but preferential flux transported bacteria to 0.45 m depth, surviving 3 weeks. Soil physical properties, irrigation system and water management will have an effect on the sanitary risk associated to reclaimed water irrigation. In this sense, subsurface drip irrigation systems (SDI) must be considered as the safest irrigation method.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)